Media Pabergiban berbantuan Model Problem Based Learning dalam Keaktifan Siswa Kelas IV - Saviola, Sandra; Dewi, Panca (PGSD FKIP UPR, 2024)
This study aims to determine the use of the Pabergiban (Papan Bermain Segi Banyak) and student activeness in learning math material using the Pabergiban media taught in fourth grade. This study is based on the problem of learning mathematics which often makes students bored and uninterested, due to the learning model chosen by the teacher tends to be monotonous and fixated on the lecture method by relying only on student books. As a result, many students do not pay attention to existing learning which will certainly have an impact on their learning outcomes. Therefore, it is necessary to choose the right media and model in the implementation of mathematics learning. So that, in this study discusses the application of the Pabergiban media assisted by the Problem Based Learning model on the material of the polygon in fourth grade. This study uses a qualitative method with a type of qualitative descriptive method so that it contains a description of the implementation of learning with the Pabergiban media assisted by the Problem Based Learning learning model and student activeness when learning is taking place. The data collection technique uses student activeness questionnaire, teacher response questionnaire, documentation and observation. The results of this study prove that students are happier when learning using concrete learning media and learning Pabergiban media used by students.